Restructuring the Lithuanian food industry: problems and perspectives - Vilija Girgzdiene (Institute of Agricultural Development in Central and Eastern Europe (IAMO), 1998)
Part of Lithuania's inheritance from the centrally planned economy of the former Soviet Union is its inefficient food processing sector, which bears much responsibility for the low competitiveness of domestic vis-à-vis imported food products. This harms the food industry itself as well as the entire agricultural sector. Consequently improvements in agriculture will only occur when efforts to increase the efficiency and technological performance of food processing bring significant results. Based on the structure-conduct-performance framework developed by the economic theory of industrial organisation, the objective of the present discussion paper is to identify those economic conditions that are giving rise to the low degree of competitiveness of Lithuanias food industry. The analysis shows that, although major progress has been made in macroeconomic stabilisation, privatisation and institution building, the efficiency and performance of this important part of the Lithuanian agro-food chain are far from perfect. Current problems of the Lithuanian food industry that result in low profitability in the food industry are increasing input costs, low labour productivity, low investment activities, excess capacities and a lack of market orientation. The main causes for these are unfavourable interest rates on bank loans, an inadeqate tax regime, ineffective corporate governance in privatised firms, and deficiencies in institution-building and implementation of institutions. – – Ein Erbe des zentralplanwirtschaftlichen Systems der ehemaligen Sowjetunion stellt der ineffiziente Verarbeitungssektor dar. Dessen Mängel sind wesentlich mit dafür verantwortlich, daß heimische nicht mit importierten Nahrungsgütern konkurrieren können. Die mangelnde Wettbewerbsfähigkeit litauischer Lebensmittel wirkt sich nicht nur auf die Ernährungsindustrie, sondern auch auf die Landwirtschaft negativ aus. Fortschritte in der Landwirtschaft sind nur dann zu erwarten, wenn entscheidende Verbesserungen in der Effizienz und Leistungsfähigkeit des Verarbeitungssektors erzielt werden. Ziel dieses Diskussionsbeitrages ist es, basierend auf dem Structure-Conduct-Performance-Ansatz der Industrieökonomik diejenigen Faktoren zu identifizieren, die zu der geringen Wettbewerbsfähigkeit der litauischen Ernährungsindustrie beitragen. Die Untersuchung zeigt, daß trotz beträchtlicher Fortschritte auf dem Gebiet der makroökonomischen Stabilisierung, der Privatisierung und dem Aufbau von Institutionen noch keine tiefgreifenden Verbesserungen der Effizienz und Leistungsfähigkeit der Ernährungsindustrie eingetreten sind. Gravierende Probleme der litauischen Ernähungsindustrie stellen steigende Inputkosten, eine niedrige Arbeitsproduktivität, eine geringe Investitionstätigkeit, Überkapazitäten und eine noch unzureichende Marktorientierung der Wirtschaftssubjekte dar. Die Gründe dafür liegen in den zu hohen Zinsen für Bankkredite, in einem ungünstigen Steuersystem, in einer ineffizienten Eigentümerstruktur der privatisierten Unternehmen und vor allem in Mängeln beim Aufbau marktwirtschaftlicher Institutionen begründet.
urn:nbn:de:gbv:3:2-22689
Keywords: 330; Nahrungsmittelgewerbe; Übergangswirtschaft; Reorganisation; Struktur-Performance-Modell; Litauen